Promosi Bimbel BIMBA AIUEO: Meningkatkan Kualitas Pendidikan Di Indonesia Berbasis Website - Raka Sayidina Riyadi; Agustine Hana Masitoh (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Education is a crucial factor in shaping the future of the younger generation. Tutoring institutions (bimbel)play an important role in supporting the teaching and learning process and optimizing students' academicpotential. Bimba AIUEO, as one of the leading tutoring institutions in Indonesia with more than twodecades of experience, has helped thousands of students achieve academic excellence, especially youngchildren who have not yet entered elementary school. With innovative teaching methods and qualifiedteaching staff, Bimba AIUEO has become the first choice for parents who want quality supplementaryeducation for their children. The creation of the Bimba AIUEO Bimba Promotion website aims to providecomplete, up-to-date, and easily accessible information about the main attractions, facilities, registration,opening hours, as well as reviews from previous alumni and also as a strategic promotional medium toface competition in the world of tutoring, making promotion an important key to reaching more prospectivestudents, and informing the added value possessed by Bimba AIUEO as a tutoring institution.